Awareness of nurses of Lithuanian perinatal centers on nosocomial infections and application of this knowledge - Čerkauskaitė, Sonata; Liepinaitienė, Alina; Tamošiūnas, Abdonas (Slauga. Mokslas ir praktika, 2020)
According to the data of the Lithuanian Institute of Hygiene, nosocomial infections, also known as hospital-acquired infections (HAI), are defined as - any illness of a bacterial, viral, parasitic, fungal origin related to the hospitalization of a patient, research, treatment in a person‘s health care institution, as well as work therein. Although the progress of modern infection control is very high, HAI remains an important public health problem. One of the most important measures of HAI management is their epidemiological surveillance, which, when properly executed, can reduce the frequency of HAI by 20-30 %. Although many means of HAI prevention have been known for a long time, systematic repetition and deepening of knowledge about basic means of HAI prevention can greatly reduce morbidity and even mortality from them. The study was conducted in April-September 2017, involving 165 nurses working in perinatal centers in Lithuania. It has been established that the knowledge the majority nurses in both Lithuanian perinatal centers have corresponds to a good or very good level of knowledge. Nurses are aware of the main means of prevention and how they are adequately adhered to, what HAI risk factors are there and in which departments it is most likely to contract HAI. However, there is a lack of knowledge about HAI transmission paths. Nurses in the 2nd center incorrectly apply knowledge related to manipulation and hand hygiene.